Factors Affecting to Students' Participation in Activities of Program in Government Mahamakut Buddhist University Lanna Campus: Factors Affecting to Students' Participation in Activities of Program in Government Mahamakut Buddhist University Lanna Campus - Poomasree, Wirat (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were 1) to study the factors influencing student participation in activities, 2) to study relationship between student and participation in activities, and 3) to suggest guidelines for promoting student participation in activities. This was a quantitative and qualitative research. The sample group consisted of 109 of 1st - 4th year students of program in government, in 2019 academic year. The research tools were questionnaires and interview forms. The statistics used to analyze the data were frequency, percentage, mean, standard deviation, and Pearson’s Product Moment Correlation Coefficient. The results of the quantitative research are as follows. The results of the quantitative research found that 1) the factors affecting to students' participation in activities were at a high level in overall. The student factor got the highest average. Participation in activities of students also was at high level. And participation in activities for arts and culture maintenance were found with the highest average. 2) The student relationship between participation in activities was a statistically significant in the same direction, and 3) The suggestions were that the university should support activities both in terms of buildings and budgets. There should be outside educational activities. There should be a meeting room in a wide area and parking place for students should have a roof. The results of the qualitative research are as follows. 1) The impressive activities were sports held both inside and outside the university. 2) The factors affecting participation in activities were the persuasion and motivation with friends in activities. 3) The university had stimulated participation in activities by providing convenient area, a good advised teacher and creative and impressive in activities.